INTRODUCTION OF LIGNOSILICON IN SOIL SIMULTANEOUSLY WITH SEEDS AND ITS INFLUENCE ON PRODUCTIVITY OF BUCKWHEAT IN ORGANIC FARMING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Lignosilicon (LSi) is biologically active product synthesized in the Latvian State Institute of Wood Chemistry on the basis of wood fuel bioethanol production waste – hydrolysis lignin. On the background of rather low dosages of LSi (40-120 kg/ha) introduced in soil simultaneously with seeds of cereals by mixing them in the box of sowing machine, plant root system developed faster and it’s volume increased significantly, plant development accelerated and the terms of corresponding stages shortened, the crop increased and it’s targeted quality went up, soil agrochemical characteristics improved as well. Due to productivity of cereals was directly connected with root system volume and it’s physiological activity, investigation of LSi effect on the agricultural plants with poorly root system as buckwheat was undertaken. The data obtained of proetein yield, content of aminoacids and dynamics of plant development have shown that lignosilicon has a good prospects for buckwheat cultivation in conditions of organic farming due to it’s ability to provide increase in crop and enhance it’s nutrition value.